Ecological characteristics of gandaria (Bouea macrophylla Griff) at dungus iwul nature reserve and yan lapa nature reserve Bogor regency - Rian Susila; Reni Srimulyaningsih; Sri Wilujeng; Raizal Fahmi (Bioscience, 2022)
Gandaria (Bouea macrophylla Griff) is the identity flora of West Java Province. Naturally, the gandaria habitat in West Java is found only in the Yan Lapa Nature Reserve (CAYL) and Dungus Iwul Nature Reserve (CADI). In the ecosystem of CADI, and CAYL the position of gandaria in the community shows a low level of dominance. The presence of invasive species in CAYL and CADI is feared will threaten the stability of ecosystems in the region in the future including the presence of native flora. This study aims to study the level of tolerance and adaptation of gandaria in nature by knowing the pattern of individual spread in the gandaria population and the type of gandaria association with other species in various environmental. This is interesting to study because of the limited efforts of species conservation and genetic conservation of gandaria, while the condition of the natural population is increasingly threatened. Individual distribution patterns in gandaria populations in CADI and CAYL are random and clustered. Gandaria at Dungus Iwul Nature Reserve and Yan Lapa Nature Reserve are positively associated with iwul, whereas the Hawuan is negatively associated. Gandaria is not associated with asam keranji, manii, kokopian, leungsir, putat, and teureup. However, gandaria is not with menteng monyet dan kitulang in CADI while in CAYL have positive position.Gandaria (Bouea macrophylla Griff) merupakan flora identitas Provinsi Jawa Barat. Secara alami, habitat gandaria di Jawa Barat hanya terdapat di Cagar Alam Yan Lapa (CAYL) dan Cagar Alam Dungus Iwul (CADI). Dalam ekosistem CADI, dan CAYL posisi gandaria dalam komunitas menunjukkan tingkat dominasi yang rendah. Kehadiran spesies invasif di CAYL dan CADI dikhawatirkan akan mengancam stabilitas ekosistem di kawasan tersebut di masa mendatang termasuk keberadaan flora asli. Penelitian ini bertujuan untuk mempelajari tingkat toleransi dan adaptasi gandaria di alam dengan mengetahui pola penyebaran individu pada populasi gandaria dan jenis asosiasi gandaria dengan spesies lain di berbagai lingkungan. Hal ini menarik untuk dikaji karena terbatasnya upaya konservasi spesies dan konservasi genetik gandaria, sedangkan kondisi populasi alaminya semakin terancam. Pola sebaran individu pada populasi gandaria di CADI dan CAYL bersifat acak dan mengelompok. Gandaria di Cagar Alam Dungus Iwul dan Cagar Alam Yan Lapa berasosiasi positif dengan iwul, sedangkan Hawuan berasosiasi negatif. Gandaria tidak diasosiasikan dengan asam keranji, manii, kokopian, leungsir, putat, dan teureup. Namun gandaria tidak dengan menteng monyet dan kitulang di CADI sedangkan di CAYL memiliki posisi positif.